Static VAR compensator using fixed structure static output feedback robust loop shaping control - Kaitwanidvilai, Somyot; Koisap, Chamnan; Ngamroo, Issarachai (My University, 2010)
This paper proposes a new technique for designing a fixed-structure static output feedback robust loop shaping controller for a power system with VAR compensator. The proposed technique uses Particle Swarm Optimization (PSO) to evaluate the final solution. Infinity norm from disturbances to states is formulated as the cost function in our optimization. The performance of the designed system is investigated in comparison with the conventional H infinity loop shaping controller, the robust controller designed by LMI method and the reduced order robust controller by Hankel norm model reduction method. As results indicated, stability margin of our proposed controller is better than that of the others. In addition, the order of the proposed controller is much lower than that of the conventional robust loop shaping controller.
Keywords: Fixed-structure robust loop shaping control; H infinity loop shaping control; Particle swarm optimization